Melaksanakan Kebersihan Bersama Masyarakat Untuk Menciptakan Lingkungan yang Sehat - Sembiring, Heka Mayasari Br; Purba, Nurita; Doloksaribu, Aida Rafelia; Maringga, Melviana; Angin, Laura Creis Agave Perangin (Lumbung Pare Cendekia, 2024)
The purpose of this community service is to invite the local community in the neighborhood of Gg. Pemda, Medan City to carry out environmental hygiene to create a healthy environment. Environmental cleaning activities have a positive impact because the environment becomes cleaner, more organized and healthier. In addition, this activity creates a sense of family and togetherness. A healthy environment arises from an environment that is clean, maintained or maintained, beautiful and well-organized. Environmental conditions are a reflection of the behavior of the people who live there. With awareness and relevant local government policies on community conditions in managing waste and environmental hygiene rules.